Pengaruh Suplementasi L-Arginine dalam Pakan terhadap Pertambahan Bobot Badan, Konsumsi Pakan dan Konversi Pakan Ayam Broiler - Charles V. Lisnahan; Alfonsus Seran; Gerson Frans Bira (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2021)
This study aims to determine the effect of L-arginine supplementation on body weight gain, feed consumption, and feed conversion of broiler chickens. The study was carried out in the farm study program of the Faculty of Agriculture for six weeks from March to May 2021. This study used 96 broiler chickens aged one day or day-old chick (DOC) strain CP 707. The method used in this study was an experiment with a completely randomized design (CRD) with a random pattern consisting of 4 treatments and four replications, so there were 16 experimental units. Each experimental unit was filled with six broiler chickens. The treatments were: T0: 100% feed BR2, T1: 99.5% feed BR2 + 0.5% L-arginine, T2: 99.25% feed BR2 + 0.75 L-arginine, T3:99.00 feed BR2 + 1.00% L-arginine. The variables observed in this study were body weight gain, feed consumption, and feed conversion of broiler chickens. The data obtained were analyzed using analysis of variance and Duncan test. The results of the analysis of variance showed that the treatment had a significant effect on body weight gain and feed conversion (P<0.05), while feed consumption had no significant effect (P>0.05). It was concluded that 0.75% L-arginine supplementation increased body weight gain and feed conversion of broilers.